United States History in the Secondary School. Politics - Point Pleasant Beach Board of Education, NJ.; Point Pleasant Beach Board of Education, NJ. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
This is one unit of the series described in SO 000 378. In this study of the American political system the principle is accepted that political parties are essential instruments for the governing and social change in a modern democratic state. Political change and development indicate a basic shift in the nature of government; this shift is motivated by demand arising out of existing conditions of industrial growth and international competition, and finds its expression in politics. The need for student realization of these principles are listed along with these objectives: 1) to develop a practical knowledge of the procedures that take place in our party system to select and elect people to office; 2) to investigate and understand that there are patterns of voting behavior; 3) to understand that the party platforms express ideas, philosophies, and concerns; 4) to realize that it is not necessary for all democracies to have the same political structures to insure individual rights; 5) to comprehend the organization and influence of political parties; 6) to investigate attempts to control political abuses; 7) to understand the role of the independent voter and the value of becoming involved in political activity. (SBE)
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Citizenship; Elections; Interdisciplinary Approach; Learning Activities; Learning Laboratories; Political Affiliation; Political Issues; Public Affairs Education; Secondary Education; Social Change; Social Problems; Social Studies; Social Systems; State Curriculum Guides; Teaching Guides; United States Government (Course); United States History; Units of Study; Voting